TECHNOLOGIES FOR THE DEVELOPMENT OF THE INSURANCE SECTOR IN THE DIGITAL ECONOMY (American Journal of Interdisciplinary Research and Development, 2022)
This paper makes analyses of the research points on insurance facilities of the Republic of Uzbekistan. On this case, improving the insurance system and its implementation mechanisms of the sector has been analysed both methodologically and theorically. Finally, research has outlined both outcomes and shortcomings as the whole.